ELECTROOPTIC CHARACTERISTICS OF COLLOIDAL SILVER SOLUTIONS USING TRANSVERSE ELECTROMAGNETIC MODE OF INCOMING LIGHT - Firdausi, K. Sofjan; Setyoningrum, Aqilatul F.D.; Tiwiyaningsih, Tiwiyaningsih; Rahmawati, Aidah; Richardina, Very; Khumaeni, Ali; Sugito, Heri; Soesanto, Qidir M.B; Azam, Much (BERKALA FISIKA, 2020)
In this paper, we demonstrated new electro-optics characteristics of silver nanoparticle solution (NPP) using linear light polarization. The electro-optical properties of NPP solution were obtained by measuring changes in the polarization of light in the transverse electromagnetic (TEM) mode, in which the source light is made linearly polarized at 0˚ and 90˚to the axis of polarizer. NPP samples were obtained by laser ablation method and electro-optical properties were obtained through high voltage DC 0-9 kV with light source from green laser pointer (532 nm). The results showed that colloidal silver solution in water at an angle mode of 0˚, strongly suspected to show active Plasmon resonance at a concentration area of 3-5 ppm, with a peak of polarization at a concentration of 4.6 ppm. In the 90˚ mode, it is assumed that the colloidal silver solution is resonant inactive, the change in polarization is caused only by a combination of natural polarization and electro-optical polarization. The study of changes in the polarization of light through electro-optical effects on silver solutions is very interesting to be developed further using other particles, because it can provide a more comprehensive answer. This method also contributes science to the new perspective of understanding the interaction of light with matter, especially colloidal silver solutions, and the like.Keywords: Light polarization, electro-optics effect, colloidal silver solution